Vaccination with DNA Encoding Truncated Enterohemorrhagic Escherichia coli (EHEC) Factor for Adherence-1 Gene (efa-1′) Confers Protective Immunity to Mice Infected with E. coli O157:H7 - Riquelme-Neira, Roberto; Rivera, Alejandra; Sáez, Darwin; Fernández, Pablo; Osorio, Gonzalo; del Canto, Felipe; Salazar, Juan C.; Vidal, Roberto M.; Oñate, Angel (Frontiers in Cellular and Infection Microbiology, 2016)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is the predominant causative agent of hemorrhagic colitis in humans and is the cause of haemolytic uraemic syndrome and other illnesses. Cattle have been implicated as the main reservoir of this organism. Here, we evaluated the immunogenicity and protective efficacy of a DNA vaccine encoding conserved sequences of truncated EHEC factor for adherence-1 (efa-1’) in a mouse model. Intranasal administration of plasmid DNA carrying the efa-1’ gene (pVAXefa-1’) into C57BL/6 mice elicited both humoral and cellular immune responses. In animals immunized with pVAXefa-1`, EHEC-secreted protein-specific IgM and IgG antibodies were detected in sera at day 45. Anti-EHEC-secreted protein sIgA was also detected in nasal and bronchoalveolar lavages. In addition, antigen-specific T-cell-proliferation, IL-10 and IFN-γ were observed upon re-stimulation with either heat-killed bacteria or EHEC-secreted proteins. Vaccinated animals were also protected against challenge with E. coli O157:H7 strain EDL933. These results suggest that DNA vaccine encoding efa-1´ have therapeutic potential in interventions against EHEC infections. This approach could lead to a new strategy in the production of vaccines that prevent infections in cattle.